Simplifying
3x + 6(x + -8) = 0
Reorder the terms:
3x + 6(-8 + x) = 0
3x + (-8 * 6 + x * 6) = 0
3x + (-48 + 6x) = 0
Reorder the terms:
-48 + 3x + 6x = 0
Combine like terms: 3x + 6x = 9x
-48 + 9x = 0
Solving
-48 + 9x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '48' to each side of the equation.
-48 + 48 + 9x = 0 + 48
Combine like terms: -48 + 48 = 0
0 + 9x = 0 + 48
9x = 0 + 48
Combine like terms: 0 + 48 = 48
9x = 48
Divide each side by '9'.
x = 5.333333333
Simplifying
x = 5.333333333